2016
DOI: 10.4236/jct.2016.73023
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Oncotype DX Recurrence Score Categories with Immunohistochemically Defined Luminal Subtypes

Abstract: Background: At the 13th St Gallen International Breast Cancer Conference in 2013, a new definition of luminal Alike and luminal B-like breast cancer was proposed, involving the expression of estrogen receptor (ER), progesterone receptor (PgR), and Ki-67. We examined the rate of concordance between the risk groups using the Oncotype DX recurrence score (RS) and the previous and newly proposed luminal subtypes with the standardized Ki-67 assessment. Method: The relationship between a previously and newly propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…If biomarker testing indicates a low risk for cancer recurrence, chemotherapy can be avoided in such patients. Oncotype DX and CanAssist Breast are known to identify high-risk patients from luminal-A like patients and low-risk patients from luminal-B like patients [ 40 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…If biomarker testing indicates a low risk for cancer recurrence, chemotherapy can be avoided in such patients. Oncotype DX and CanAssist Breast are known to identify high-risk patients from luminal-A like patients and low-risk patients from luminal-B like patients [ 40 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…Given the rarity of the histotype, the case was subjected to a second anatomopathological review at another hospital, which confirmed the histopathological characteristics reported. Given that luminal A-like tumors are more likely low-grade and with low RS than luminal B-like tumors [ 41 ], by subjecting this case to Oncotype Dx, we expected to obtain a low RS. We obtained an intermediate RS of 23, which, combined with the patient’s age of 49, suggested a chemotherapy benefit of approximately 6.5%.…”
Section: Discussionmentioning
confidence: 99%